The Effect of Firm Value, Free Float, and Ownership Concentration on Stock Volatility: A Systematic Literature Review - Yohanes Arts Abimanyu; Hapzi Ali (Dinasti Accounting Review, 2026)
This study examines the relationships between firm value, free float, and ownership concentration and stock volatility to clarify how firm fundamentals and ownership structures shape stock market risk. It aims to develop conceptual hypotheses for subsequent empirical research through a synthesis of prior studies. The study adopts a library research design using a Systematic Literature Review (SLR) approach. Literature was retrieved from Google Scholar, journal publisher websites, article DOIs, e-books, and other online academic databases; Mendeley was used to manage references. The selected studies were analyzed descriptively and qualitatively, with evidence classified as direct, indirect, or conditional. The review indicates that: (1) firm value is associated with stock volatility through market valuation, growth opportunities, and information uncertainty; (2) free float may influence stock volatility through liquidity, market depth, and the availability of publicly tradable shares; and (3) ownership concentration may influence stock volatility through monitoring mechanisms, information asymmetry, minority shareholder protection, and trading structure. Direct evidence for free float and ownership concentration remains limited; therefore, both relationships require further empirical examination.